2010
DOI: 10.1042/cs20100248
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis and sex hormones: current concepts

Abstract: CVD (cardiovascular disease) is the leading cause of death for women. Considerable progress has been made in both our understanding of the complexities governing menopausal hormone therapy and our understanding of the cellular and molecular mechanisms underlying hormone and hormone receptor function. Understanding the interplay of atherosclerosis and sex steroid hormones and their cognate receptors at the level of the vessel wall has important ramifications for clinical practice. In the present review, we disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 197 publications
0
97
2
4
Order By: Relevance
“…The incidence of cardiovascular diseases in women increases after 50 years of age (19). This increased risk can be attributed to a decline in the estrogen levels after the menopausal transition (20). The studies carried out in postmenopausal women have reported an inverse relation between estrogen levels, dyslipidemia, and atherosclerosis (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of cardiovascular diseases in women increases after 50 years of age (19). This increased risk can be attributed to a decline in the estrogen levels after the menopausal transition (20). The studies carried out in postmenopausal women have reported an inverse relation between estrogen levels, dyslipidemia, and atherosclerosis (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Estradiol alone has little effect on the production of androgen receptor (Wynne and Khalil 2003). The concentration of AR is less in females than males and it appears to be regulated by a combination of estradiol and testosterone (Villablanca et al 2010). …”
Section: General Conceptsmentioning
confidence: 99%
“…DHT has a higher affinity for AR and is converted from testosterone in target cells (Imperato-McGinley and Canovatchel 1992). Androgen receptors (AR) have been identified in vascular endothelial cells, vascular smooth muscle cells (VSM), macrophages and monocytes (Villablanca et al 2010). Estradiol alone has little effect on the production of androgen receptor (Wynne and Khalil 2003).…”
Section: General Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of the research, scholars believe that androgen retard atherosclerosis of postmenopausal women, improve coronary heart disease and ischemic cerebral infarction prognosis [9].…”
Section: Coronary Heart Disease In Postmenopausal Womenmentioning
confidence: 99%